Resource Assignment Schemes for Pre-configured Backup Protection in Elastic Optical Networks - Suthaharan, S. (11th International Conference on Industrial and Information Systems (ICIIS), 2016)
In this paper, the problem of providing survivability in elastic optical networks (EONs) is addressed. EONs use 12.5 GHz fine granular frequency slots or flexible grids instead of using the traditional 50 GHz fixed grid networks and therefore frequency spectrum is used more efficiently. For providing survivability, a recently proposed survivability scheme known as pre-configured backup protection with sharing (PBPS) is considered because of its benefits over traditional approaches. In PBPS, backup paths can be pre-configured and they can share resources simultaneously. Therefore, both short recovery time and efficient resource usage can be achieved. Resource assignment is a potential issue in which primary and backup paths can be provisioned in various schemes. Resource assignment using First-Fit scheme for the primary and for the backup paths has earlier been studied in PBPS with flexgrid (EONs) networks. Assigning resources for the primary and for the backup paths deploying First-Fit and Last-Fit schemes has already been investigated in only shared protection with flexgrid networks. However, resource assignment to use First-Fit scheme for the primary path and to use Last-Fit scheme for the backup path using PBPS in flexgrid networks has not been investigated and this investigation is the focus of this paper. This investigation includes detailed simulation experiments on different networks topologies. The findings are as follows. Significant blocking reduction is seen in PBPS with EONs using First-Fit for primary path and Last-Fit for backup path when compared to assigning resources using First-Fit for both primary and backup paths. Further, particularly in high network loads, even more blocking reduction is seen when compared to low network loads in all the networks topologies.
Keywords: elastic optical networks; survivability; resource assignment schemes